WHY MERELY TOLERANCE? - Maria BARBU CIURCHEA (Studia Universitatis Babeș-Bolyai. Philosophia)
Why Merely Tolerance? The present paper discusses two possible responses to ethical pluralism. Starting from the premise that there exists a multitude of irreducible moral values, the paper analyzes two of the possible responses to this fact, namely ethical promiscuity and tolerance. The first one, as defined by Ivanhoe, promises to outdo tolerance and to solve the insufficiencies of the latter. However, the paper analyzes the main claims and arguments in favor of ethical promiscuity, putting in light the fact that this view does not actually manage to deal with the problem of clashing and mutually excluding moral values.